Cultural foundations of welfare: The role of traditional values and community norms in shaping elderly well-being in China - Anqi, Ming; Pasitpakakul, Pattama; Jintana, Sanitdech (Edelweiss Applied Science and Technology, 2025)
As China deals with a rapidly aging population, understanding the cultural factors that influence elderly welfare is becoming increasingly important. This study examines how Traditional Family Values (TFV) and Community Cultural Norms (CCN) affect Elderly Welfare Outcomes (EWO). It focuses on the roles of Policy Awareness (PA) and Policy Implementation (PI) in this process. The research was conducted in Zigong, a city with diverse demographics, using a stratified sampling method to represent different ethnic, socioeconomic, and urban-rural groups. Data were collected from 513 elderly individuals and analyzed using Structural Equation Modeling (SEM) through SmartPLS to test ten proposed relationships. The results indicate that TFV has a direct positive effect on EWO, but its influence through PA and PI is less significant. Conversely, CCN has a greater impact on welfare outcomes by enhancing policy awareness and implementation. These findings suggest that being informed about public policies strengthens the positive effects of cultural norms on elderly welfare. The study concludes that increasing policy literacy and adopting inclusive implementation strategies can help translate cultural alignment into tangible welfare improvements. This provides practical insights for policymakers aiming to develop aging policies that address cultural needs.